Spatiotemporal impact on yield stability of intercropped cocoa (Thoebroma cocoa L.) in cyclone prone Indian East Coastal terrains - Arun Kumar, R.; Kireeti, A.; Babu, R.; Surulirajan, M.; Sumitha, R.; Elian Apshara, S.; Jerard, B. A. (Journal of Plantation Crops, 2026)
Cocoa (The cocoa) is cross pollinated, perennial and promising inter crop in coconut garden six types viz., VTLCH 1-4, VTLCC1 and VTLC- 1 was received from Regional Station working under ICAR-CPCRI, Vittal and planted at Coconut Research Station, Veppankulam in 2008. Single row system of cocoa was inter-cropped in coconut variety ECT. Thirteen critical biometric and yield related parameters were recorded. As per the AICRP trial for bio metric parameters the data for the year 2022- 23 was analysed and descriptive statistics was discussed. The yield of past four years i.e yield after GAJA cyclone was taken into consideration to analyse the stability of cocoa varieties and to identify superior types suitable for the East coast Tall. Among the various types, the genotypes Tc2 (VTLCH 1), highest mean yield (1.58 kg tree⁻¹ year⁻¹), compared to the lowest in Tc6 (0.96 kg tree⁻¹ year⁻¹). Descriptive statistics indicated moderate variability (CV = 17.72%) for yield. Stability analysis using parametric models showed that Tc2 possessed a regression coefficient less than unity (βᵢ = 0.55), low deviation from regression (S²dᵢ = 0.80), and low coefficient of variation (2.03%), indicating high adaptability under stress conditions. Variance-based parameters further supported its stability, with low θᵢ (19.78), Wᵢ² (24.66), and σ²ᵢ (2.81), coupled with high θ₍ᵢ₎ (30.32), reflecting minimal genotype × environment interaction. Non-parametric stability measures (S and NP indices) and Kang’s rank-sum method also ranked Tc2 as the most stable genotype. Positive correlations between yield and traits such as canopy spread, trunk girth, and pod characteristics emphasized their role in stress recovery and productivity. Overall, Tc2 demonstrated superior yield stability and resilience, making it a suitable genotype for cultivation in cyclone-prone coastal ecosystems and a valuable candidate for climate-resilient breeding programs.